2016
DOI: 10.3389/fpsyg.2016.00258
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Using Spatial and Verbal Abilities Influence Route Learning Performance in a Virtual Environment: A Comparison of 6- to 12-Year Old Boys and Girls

Abstract: Previous studies have reported sex differences in wayfinding performance among adults. Men are typically better at using Euclidean information and survey strategies while women are better at using landmark information and route strategies. However, relatively few studies have examined sex differences in wayfinding in children. This research investigated relationships between route learning performance and two general abilities: spatial ability and verbal memory in 153 boys and girls between 6- to 12-years-old.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 81 publications
(120 reference statements)
5
41
0
Order By: Relevance
“…In modern-day life, males may no longer need to hunt, but they still prefer activities involving spatial processing such video games and sports (Okagaki and Frensch, 1994; Ozel et al, 2004; Robert and Héroux, 2004; Cherney and London, 2006), which may have continued to help males gain an advantage in spatial ability. Males and females have also been found to use different strategies when performing a navigation task, with males using spatial strategies and females using both verbal and spatial strategies (Merrill et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In modern-day life, males may no longer need to hunt, but they still prefer activities involving spatial processing such video games and sports (Okagaki and Frensch, 1994; Ozel et al, 2004; Robert and Héroux, 2004; Cherney and London, 2006), which may have continued to help males gain an advantage in spatial ability. Males and females have also been found to use different strategies when performing a navigation task, with males using spatial strategies and females using both verbal and spatial strategies (Merrill et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that large-scale abilities (like path learning) are related to small-scale abilities (Hegarty et al, 2006), which include a large set of skills used in basic processing, such as WM, and higher-level functions like mental rotation (Hegarty and Waller, 2005). The relation between small-scale (spatial) abilities and environment learning performance has been demonstrated in adults (Hegarty et al, 2006;Weisberg et al, 2014) as well as in developmental age, in 5-6 years old children (e.g., Fenner et al, 2000;Purser et al, 2012Purser et al, , 2015Merrill et al, 2016;Thomas et al, 2016), albeit with some inconsistencies in the findings. In a recent study, Merrill et al (2016) found that the visuo-spatial abilities -i.e., mental rotation, spatial visualization (the ability to arrange spatial stimuli), and visuo-spatial working memory (in a task resembling those used to test simultaneous WM) -of children 6-12 years old were related to their path learning accuracy (after exploring VE), but it was only in females that verbal WM was also a significant predictor of their performance.…”
Section: The Role Of Cognitive Abilities In Supporting Path Learningmentioning
confidence: 99%
“…The relation between small-scale (spatial) abilities and environment learning performance has been demonstrated in adults (Hegarty et al, 2006;Weisberg et al, 2014) as well as in developmental age, in 5-6 years old children (e.g., Fenner et al, 2000;Purser et al, 2012Purser et al, , 2015Merrill et al, 2016;Thomas et al, 2016), albeit with some inconsistencies in the findings. In a recent study, Merrill et al (2016) found that the visuo-spatial abilities -i.e., mental rotation, spatial visualization (the ability to arrange spatial stimuli), and visuo-spatial working memory (in a task resembling those used to test simultaneous WM) -of children 6-12 years old were related to their path learning accuracy (after exploring VE), but it was only in females that verbal WM was also a significant predictor of their performance. Fenner et al (2000) also found visuo-spatial abilities (including visualization, mental rotation and tasks resembling those used to test sequential WM) related to path learning (after exploring VE) in 5-6 years old, but not in 8-9 year old children.…”
Section: The Role Of Cognitive Abilities In Supporting Path Learningmentioning
confidence: 99%
“…Though further research is certainly needed on the role of small-scale (spatial cognitive) abilities in successful path learning, our results support the spatial cognition model postulating a relationship between small-and large-scale abilities not only in young adults (Hegarty et al, 2006), and TD children (Merrill et al, 2016), but also in cases of atypical development. This relationship can be demonstrated using VE , and also -as our study newly showed -using actual movements in the environment.…”
Section: Discussion Of the Results And Conclusionsupporting
confidence: 80%